Overall survival by pattern of recurrence following curative intent surgery for colorectal liver metastasis. Issue 8 (21st August 2014) - Kulaylat, Afif N.; Schubart, Jane R.; Stokes, Audrey L.; Bhayani, Neil H.; Wong, Joyce; Kimchi, Eric T.; O'Carroll, Kevin F. Staveley; Kaifi, Jussuf T.; Gusani, Niraj J.
<x xml:space="preserve">Abstract</x> Background Following curative intent surgery (CIS) for colorectal liver metastasis (CRLM), patterns of recurrence and subsequent survival outcomes are not widely reported. Methods An institutional database (January 2002–December 2012) was reviewed to evaluate patterns of recurrence following CIS for CRLM. Results 163 patients with CRLM underwent successful CIS. Median follow‐up and disease‐free interval were 33 and 16 months, respectively. 5‐year overall survival (OS) was 55%. After initial CIS, 102 (63%) patients recurred: liver‐44% (5‐year OS 55%), lung‐15% (5‐year OS 45%), and other/multifocal‐41% (5‐year OS 24%). OS for isolated liver and lung recurrences were not significantly different. Liver only recurrence was associated with 1–5 mm liver resection margins (P = 0.048). Lung only recurrence was associated with extrahepatic metastasis (at the time of initial CRLM) (P = 0.025). Other/multifocal recurrence was associated with bilobar CRLM (P = 0.026), and extrahepatic metastasis (P = 0.028). Conclusions Patterns of recurrence following CIS for CRLM have important implications for OS. 5‐year OS was similar between isolated lung and liver recurrences. During CIS, decreased liver resection margin may be associated with increased risk of liver only recurrence. Patients with aggressive primary or metastatic liver disease are at higher risk for pulmonary or other/multifocal recurrence. J. Surg. Oncol. 2014; 110:1011–1015. © 2014 Wiley Periodicals, Inc.